Field cooling-induced magnetic anisotropy in exchange biased CoO/Fe bilayer studied by ferromagnetic resonance - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Exchange-biased CoO/Fe bilayer grown on MgO (0 0 1) substrate by sputtering, studied by variable angle and temperature ferromagnetic resonance. Room temperature in-plane measurements reveal that the Fe layer was epitaxially grown on MgO substrate with a fourfold cubic symmetry. The data also show that the easy axis of magnetization is in the film plane and makes an angle of 45 degrees with the [1 0 0] crystallographic direction of MgO substrate. The low temperature data exhibit a sudden onset of a field cooling-induced and shifted cubic anisotropy below the Neel temperature of CoO. This results in a two fold uniaxial or fourfold cubic symmetry for in-plane magnetic anisotropy depending on a field cooling direction. Low temperature measurements also present a reduction in the resonance fields due to the antiferromagnetic/ferromagnetic coupling. The developed theoretical model perfectly simulates the experimental data of coupled CoO/Fe bilayer. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ferromagnetic resonance; Magnetic properties of thin film; Magnetic anisotropy; Exchange bias